Scientific initiation in the context of emergency remote teaching: report of experience of exploitation of digital literatures (Research, Society and Development, 2021)
This work aims to provide an experience report on the exploration of digital literacies in the context of emergency remote education (ERE), presenting the perception of scholarship students about Scientific Initiation (SI) activities carried out through Digital Information Technologies and Communication (DITC). The relevance of the theme is justified by the pressing need for changes in the educational sphere, due to the COVID-19 pandemic. The epistemological anchorage comes from theories that discuss scientific initiation, digital literacies and the videominute discursive genre, proposed by the national guiding document, National Common Curriculum Base (NCCB). The chosen research methodology is qualitative, empirically based, arising from the experience report of SI students. The analysis categories were “academic training and digital literacy”. The investigation results pointed to the usefulness of digital literacies in SI in the teaching and learning process of the undergraduate student, as it impacted on academic training, in the professional sphere and awakened to the continuation of studies at the post-graduation level. Regarding the pandemic context, the methodological path indicated that it required disruptive changes that evoked the domain of digital literacies, changing the practice of researchers and indicating the need for better preparation of those involved, through the multiple digital literacies required in the digital sphere, in a small amount of time.